Les spécificités des formations hybrides en langues - Elke Nissen (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Blended language learning (BLL) courses take advantage, at the same time, of their digital and distant component and of a strong human presence. Several examples illustrate the great variability of this type of courses. BLL courses have nevertheless some common specific features, that are highlighted and analyzed in the field’s literature.